New realization scheme of pseudo-chaotic-based encoder and decoder for UWB communications - JIANG Guo-ping1; WAN Dong-dong1; XUE Long1 (Tongxin xuebao)
Chaos-modulation-based ultra wide band （UWB） communication was addressed.A new structure for the pseudo-chaotic encoder was presented,and some decoding schemes were also given accordingly.The performances of such decoding schemes were compared in the AWGN channel.Simulation results verify and demonstrate the effectiveness of the proposed method.